2005
DOI: 10.17221/3991-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Model parameters of growth curves of three meat-type lines of Japanese quail

Abstract: This study was focused on a comparison of the growth characteristics and parameters of three meat-type lines of Japanese quail. The body weight data of wild-type, dotted-white and extended-brown quail lines over time were collected and fitted to Richards equation. The relevant parameters were compared based on the Confidence Interval Test. Confidence Interval Test calculates the percentages of model predictions staying in the confidence intervals of the corresponding experimental data. Both sexes of brown quai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 16 publications
7
22
1
Order By: Relevance
“…Sexual dimorphism has previously been reported in favour of the male in duck [23], pigeon [24], and pheasants [25,26]. The growth pattern of male and female Japanese quails raised in other environments have been well documented [20,[27][28][29]. The growth pattern observed in the present study agrees with the pattern reported in refs.…”
Section: Discussionsupporting
confidence: 91%
“…Sexual dimorphism has previously been reported in favour of the male in duck [23], pigeon [24], and pheasants [25,26]. The growth pattern of male and female Japanese quails raised in other environments have been well documented [20,[27][28][29]. The growth pattern observed in the present study agrees with the pattern reported in refs.…”
Section: Discussionsupporting
confidence: 91%
“…So it showed that ST breed got higher weight then the SCW breed and also the growth rate (Tables 3-5), was faster in ST than the SCW. According to logistic, Gompertz and Bertalanffy the female reached the inflection point faster than the male but in Richards that was opposite in which male reached the inflection point faster than the female; that was also reported by Sezer & Tarhan (2005) in quail. That difference in inflection point could be due to Richards shape parameter (d), as it has greater propensity to change in response to environment, Wang et al (2012).…”
Section: Model Parametersmentioning
confidence: 76%
“…These results were in disagreement with the previous theory that stated Gompertz equation was the best fit for galiforms (Tzeng and Becker, 1981;Ricklefs, 1985;Anthony et al, 1991;Akbas and Oguz, 1998;Dogan et al, 2010). Brisbin et al (1986), Knízetová et al (1991aKnízetová et al ( , 1991b, Darmani-Kuhi et al (2003), Balcioğlu et al (2005), Sezer and Tarhan (2005) and Darmani-Kuhi et al (2010) successfully fitted Richards function to the poultry growth data. Further, in unselected quail population, Dogan et al (2010) were compared different growth functions and reported that Gompertz was the best function followed by Richards, and H3.…”
Section: Discussionmentioning
confidence: 99%